Understanding CancelRx: Results of End-to-End Functional Testing, Proactive Risk Assessment, and Pilot Implementation - Pitts, Samantha I.; Barasch, Noah; Maslen, Andrew T.; Thomas, Bridgette A.; Dorissaint, Leonard P.; Decker, Krista G.; Kazi, Sadaf; Yang, Yushi; Chen, Allen R. (Applied Clinical Informatics, 2019)
Background CancelRx allows prescribers to send electronic cancellation messages to pharmacies when medications are discontinued. Little is known about its functionality and impact on clinical workflows.Objectives To understand CancelRx functionality, its potential impact on workflows and medication safety risks, and to develop mitigating strategies for risks introduced by implementation.Methods We conducted direct observations and semi-structured interviews to develop CancelRx use cases and assessed CancelRx in an end-to-end test environment, proactive risk assessment, and pilot implementation from April 16 to July 15, 2018.Results E-cancellations were sent upon discontinuation of e-prescriptions written within the electronic health record (EHR), but not other medications (e.g., printed prescriptions) and could be initiated by nonprescribers. In our proactive risk assessment, CancelRx implementation eliminated five of seven failure modes in outpatient prescribing to Johns Hopkins pharmacies, but introduced new risks, including (1) failure to act if an e-cancellation was not sent or was unsuccessful; (2) failure to cancel all prescriptions for a medication; (3) errors in manual matching; and (4) erroneous medication cancellations. We identified potential mitigation strategies for these risks. During pilot implementation, 92.4% (428/463) of e-cancellations had confirmed approval by the receiving pharmacy, while 4.5% (21/463) were denied, and 3.0% (14/463) had no e-cancellation response. Among e-cancellations received by the pilot pharmacy, 1.7% (7/408) required manual matching by pharmacy staff. Based on performance in testing, 73.4% (340/463) of completed e-cancellations would be expected to generate an in-basket message, including 21 (6.2%) denials and 319/340 (93.8%) approvals with a note from the pharmacy.Conclusion CancelRx is an important functionality with the potential to decrease adverse events due to medication errors. However, changes in implementation in our EHR and pharmacy software and enhancements in the CancelRx standard are needed to maximize safety and usability. Further studies are needed to evaluate the impact of e-cancellation on medication safety.
Keywords: electronic prescribing; medication errors; risk assessment